Comparative study of cytogenetic biomonitoring in veterinary personnel occupationally exposed to ionizing radiation by cytokinesis-block micronucleus assay - Chaves Campos, Fabio Andrés (2022)
Introduction: Ionizing radiation (RI) can induce the formation of micronuclei (MN). The formation of MN is used as a biomarker of radiation-induced genetic damage. Objective: assess DNA damage resulting from occupational exposure to RI in veterinary personnel. Methodology: the cytokinesis-block micronucleus assay (MNBC) was used to compare the observed frequency of MN in 40 individuals occupationally exposed to ionizing radiation with respect to a control group of 32 participants, both groups belonging to veterinary personnel. In addition, demographic, lifestyle and occupational variables that could influence the formation of MN were recorded. Results: univariate analysis did not show significant differences in the frequency of MN between the study groups (p=0.118). Using multivariate analysis, it was found that approximately 27% (adjusted R2= 0.269) of the variability in the frequency of MN can be explained by the joint influence of age, sex and the number of radiographic images performed by the participant. Age is the variable with the greatest relative importance (β = 0.504), followed by the sex of the participant (β = -0.316) and the number of X-rays performed per day (β = 0.214). Conclusions: the frequency of MN tends to increase in women, as the participant's age increases and as the number of radiographic images performed increases.